EFQM EXCELLENCE MODEL AS A BASIS FOR SELF-ASSESSMENT: A STUDY OF ELECTROMECHANICAL SECTOR IN TURKEY - (:unkn) unknown (EUROMED PRESS, 2013)
Because of the increasing demand for energy in Turkey as well as in the world, production and distribution sectors of energy have been developing rapidly and continuously for long years. By this study, it is aimed to get a snapshot of Total Quality Management activities of Turkey's low voltage equipment producers in electromechanical sector. In this study, research is done under the circumstances of Excellence Model developed by European Foundation for Quality Management and its self-assessment form is used as survey tool. Amongst the findings are that many companies are aware of TQM in management and national and international quality awards encourage them on their journey towards quality. It was also found that companies from this sector should improve themselves on leadership, people and partnerships & resources criteria in order to gain competitive advantage.
Keywords: TQM; EFQM Business Excellence; Turkey's electromechanical sector; self-assessment